2003
DOI: 10.1007/s00441-002-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of serotonin and its possible role in early embryos of Tritonia diomedea (Mollusca: Nudibranchia)

Abstract: A classical neurotransmitter serotonin (5-HT) was detected immunochemically using laser scanning microscopy at the early stages of Tritonia diomedea development. At the one-to eight-cell stages, immunolabeling suggested the presence of 5-HT in the cytoplasm close to the animal pole. At the morula and blastula stages, a group of micromeres at the animal pole showed immunoreactivity. At the gastrula stage no immunoreactive cells were detected, but they arose again at the early veliger stage. Antagonists of 5-HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…9 ([ 31 , 62 64 ], present data)), and in the hyposphere (caudally or caudo-laterally) in gastropods and polyplacophores (scenario 3 on Fig. 9 [ 57 , 65 , 66 ]). Important, the primary location of the sensory pioneer neurons in larvae is largely irrelevant, while the way of their neurites will ultimately mark a position of VNC, albeit through different pathways (dorso-ventral direction or posterior-anterior direction).…”
Section: Discussionmentioning
confidence: 83%
“…9 ([ 31 , 62 64 ], present data)), and in the hyposphere (caudally or caudo-laterally) in gastropods and polyplacophores (scenario 3 on Fig. 9 [ 57 , 65 , 66 ]). Important, the primary location of the sensory pioneer neurons in larvae is largely irrelevant, while the way of their neurites will ultimately mark a position of VNC, albeit through different pathways (dorso-ventral direction or posterior-anterior direction).…”
Section: Discussionmentioning
confidence: 83%
“…Serotonin is present in all species of early embryos studied (Buznikov, 1989). In particular in sea urchins it is distributed over the cytoplasm (Buznikov et al , 1979; Markova et al , 1985; Buznikov et al , 2003; Amireault & Dubé, 2005). The present immunohistochemical research showed the uniform localization of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed results from Buznikov's and other laboratories provided pharmacological and immunocytochemical evidence in developing embryos and larvae from sea urchin species of a pre-nervous serotoninergic system, a multifunctional regulator of key events in early embryogenesis, whose action is mediated by 5-HT receptors or transporters (Renaud et al 1983;Buznikov et al 1996Buznikov et al , 2001Buznikov et al , 2005Yaguchi et al 2000;Katow et al 2004). Similar data were obtained in other invertebrate species, and this neurochemical has been shown to participate in the control of oocyte maturation (Krantic et al 1993;Leclerc et al 2000;Stricker & Smythe 2000) and fertilization (Leclerc et al 2000), and to act as a regulator of cleavage division (Buznikov et al 2003) and of cell movement during gastrulation (Colas et al 1999a, b). The ability of neurotransmitters to regulate basic developmental processes before the appearance of neurons seems to be conserved across animal taxa.…”
mentioning
confidence: 77%